Extracorporeal life support as a bridge to pulmonary retransplantation: prognostic factors for survival in a multicentre cohort analysis. (22nd December 2021) - Inci, Ilhan; Ehrsam, Jonas Peter; Van Raemdonck, Dirk; Ceulemans, Laurens Joseph; Krüger, Thorsten; Koutsokera, Angela; Schiavon, Marco; Faccioli, Eleonora; Nosotti, Mario; Rosso, Lorenzo; D'Ovidio, Frank; Leiva-Juarez, Miguel; et al.
Abstract: : OBJECTIVES: Pulmonary retransplant (ReTx) is considered a controversial procedure. Despite literature reporting outcomes following ReTx, limited data exist in recipients bridged to their ReTx on extracorporeal life support (ECLS). The goal of this study was to investigate the outcomes of recipients bridged to a first-time ReTx by ECLS. METHODS: We performed a retrospective multicentre cohort analysis from 10 centres in Europe, Asia and North America. The primary outcome was overall survival. Risk factors were analysed using Cox regression models. RESULTS: ECLS as a bridge to a first-time ReTx was performed in 50 recipients (ECLS-ReTx). During the study period, 210 recipients underwent a first-time ReTx without bridging on ECLS (regular-ReTx) and 4959 recipients had a primary pulmonary transplant (index-Tx). The overall 1-year (55%) and 5-year (29%) survival was significantly worse for the ECLS-ReTx group. Compared to the index-Tx group, the mortality risk was significantly higher after ECLS-ReTx [hazard ratio 2.76 (95% confidence interval 1.94–3.91); P < 0.001] and regular-ReTx [hazard ratio 1.65 (95% confidence interval 1.36–2); P < 0.001]. In multivariable analysis, recipient age ≥35 years, time interval <1 year from index-Tx, primary graft dysfunction as transplant indication, venoarterial-extracorporeal membrane oxygenation and Zurich donor score ≥4 points were significant risk factors for mortality in ECLS-ReTx recipients. CONCLUSIONS: Recipients for ECLS-ReTx should be carefully selected. Risk factors, such as recipient age, intertransplant interval, primary graft dysfunction as transplant indication and type of ECLS should be kept in mind before bridging these patients on ECLS to ReTx. Abstract : Increased lung transplants (LTxs) and improved survival have led to the need for retransplants (ReTxs) because ∼50% of these recipients suffer from chronic lung allograft rejection by 5 years [1, 2].